A secure blockchain-enabled vehicle identity management framework for intelligent transportation systems. (January 2023) - Das, Debashis; Dasgupta, Kousik; Biswas, Utpal
Highlights: The identity generation method for vehicles aims to process of verification and validation of the identity. The UID needs to be generated only once and can be shared any number of times for authentication until it expires. Enable the user to have control of data sharing identities and shared data. Ensures the correctness and validity of the Personal Identifiable Information. Ensures the reliability and trustworthiness of such identity by securing the correct mapping of a user. Abstract: The need for secure and reliable identity management and authentication scheme for vehicles is becoming increasingly prominent with the digitization of the Intelligent Transportation System (ITS) in smart cities. Today, ITS is extensively acknowledged and employed in a variety of nations. Several existing ITS solutions in smart cities have observant limitations such as trust, security, threats, and centralization platform that can be vulnerable to the authentication and validation of vehicles. The differentiation in compatibility and requirement of IoT-based applications/services produced different challenges for establishing a uniform standard for data exchange, data usage, encoding mechanisms, and data storage for the identity management of vehicles. In this paper, identity generation and management methods are proposed using Blockchain to address existing challenges in ITS applications prevailing with the security of existing identity management and authentication of vehicles. The proposed solution focuses mainly on assurance of the validity of Personal Identification Information (PII) used for producing identity and usability of the application to make the solution suitable to raise the vehicle administration in the ITS. The experiment results and performance analysis represent that the proposed method ensures the correctness and validity of the PII and ensures the reliability and trustworthiness of such identity by securing the correct mapping of a user.